2009
DOI: 10.1038/jcbfm.2009.262
|View full text |Cite
|
Sign up to set email alerts
|

Role of CCL2 (MCP-1) in Traumatic Brain Injury (TBI): Evidence from Severe TBI Patients and CCL2−/− Mice

Abstract: Cerebral inflammation involves molecular cascades contributing to progressive damage after traumatic brain injury (TBI). The chemokine CC ligand-2 (CCL2) (formerly monocyte chemoattractant protein-1, MCP-1) is implicated in macrophage recruitment into damaged parenchyma after TBI. This study analyzed the presence of CCL2 in human TBI, and further investigated the role of CCL2 in physiological and cellular mechanisms of secondary brain damage after TBI. Sustained elevation of CCL2 was detected in the cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
273
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(303 citation statements)
references
References 41 publications
23
273
3
4
Order By: Relevance
“…The influx of these inflammatory cells is driven by monocyte chemoattractants, such as CCL2, whose synthesis is rapidly increased in the injured cortex (Semple et al, 2010a;Szmydynger-Chodobska et al, 2010). In the present study, we demonstrated that neurotrauma also results in a rapid increase in production of CCL2 by the lateral ventricle CP located ipsilaterally to injury.…”
Section: Discussionsupporting
confidence: 59%
“…The influx of these inflammatory cells is driven by monocyte chemoattractants, such as CCL2, whose synthesis is rapidly increased in the injured cortex (Semple et al, 2010a;Szmydynger-Chodobska et al, 2010). In the present study, we demonstrated that neurotrauma also results in a rapid increase in production of CCL2 by the lateral ventricle CP located ipsilaterally to injury.…”
Section: Discussionsupporting
confidence: 59%
“…Mice deficient in CXC receptor 2 which interacts with chemokines CXCL8, CXCL1 and CXCL2 and mediates the neutrophil transmigration across the BBB were reported to demonstrate significant attenuation of neutrophil infiltration, reduced tissue damage and neuronal loss, especially in the delayed phase post injury (Semple et al, 2010a). In a similar study, deletion of monocyte chemokine CCL2 gene resulted in improved neurological function, delayed reduction in lesion volume and macrophage accumulation (Semple et al, 2010b). Both the latter studies support the notion that late inhibition of leukocyte recruitment in TBI may be beneficial for the extent of brain trauma and the clinical outcome.…”
Section: Neuroinflammationmentioning
confidence: 51%
“…Increased concentrations of inflammatory proteins, such as IL-6, IL-8, and IL-10, in the CSF following injury have been reported in many studies (87)(88)(89)(90)(91)(92)(93). It is unclear if this immune response is a result of local production of immune mediators or leakage of these proteins across a compromised BBB.…”
Section: Biomarkers Of Neuroinflammationmentioning
confidence: 99%